Gall midges of subfamily Lestremiinae from Estonia, Latvia and Lithuania: checklist and description of new species (Diptera: Cecidomyiidae). - Spungis, Voldemars; Jaschhof, Mathias (Contributions to Entomology = Beiträge zur Entomologie, 2000)
A total of 116 gall midge species belonging to the subfamily Lestremiinae (Cecidomyiidae) are reported from the East Baltic region, 48 species from Estonia, 113 from Latvia, and 42 from Lithuania. Additionally, information on the morphology of adults is given for the following species: Aprionus barbatus, A. betulae (description of female), A. complicatus, A. inquisitor, A. insignis (description of female), A. laevis, A. onychophorus (including description of female), A. tiliamcorticis, Lestremia parvostylia (description of female), Monardia (Monardia) monilicornis (including description of male), Neurolyga bilobata (including description of female), and Peromyia subborealis. Three new species are described: Groveriella baltica sp. n., Heterogenella multifurcata sp. n., and Strobliella brachycornis sp. n.KeywordsDiptera, Cecidomyiidae, Lestremiinae, Estonia, Latvia, Lithuania, checklist, new species.Nomenclatural Actsbaltica Spungis & Jaschhof, 2000 (Groveriella), spec. n.multifurcata Spungis & Jaschhof, 2000 (Heterogenella), spec. n.brachycornis Spungis & Jaschhof, 2000 (Strobliella), spec. n.